2017
DOI: 10.5051/jpis.2017.47.96
|View full text |Cite
|
Sign up to set email alerts
|

Association between periodontal flap surgery for periodontitis and vasculogenic erectile dysfunction in Koreans

Abstract: medical checkup data from 2002 to 2013 were used to evaluate the association between periodontal surgery for the treatment of periodontitis (PSTP) and vasculogenic erectile dysfunction (VED). Methods: Bivariate and multivariate logistic regression analyses were applied to a longitudinal retrospective database to assess the association between PSTP and VED while adjusting for the potential confounding effects of sociodemographic factors (age, household income, insurance status, health status, residence area, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…A total of 74 percent ( n = 38) of all included studies applied a cohort design . In addition, seven studies reported a case–control design, five studies reported a cross‐sectional, and one study a case‐crossover design . Two studies reported a cohort design, but because the exposure and outcome variables were collected over the same time period and no time‐related reference could be made, these studies were classified as cross‐sectional designs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 74 percent ( n = 38) of all included studies applied a cohort design . In addition, seven studies reported a case–control design, five studies reported a cross‐sectional, and one study a case‐crossover design . Two studies reported a cohort design, but because the exposure and outcome variables were collected over the same time period and no time‐related reference could be made, these studies were classified as cross‐sectional designs.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies could not be assigned to one of the areas listed above as they were based on a cross‐sectional design …”
Section: Resultsmentioning
confidence: 99%
“…Also, the evidence about the role of ED and periodontitis is scarce in European population, because the majority of the studies have been performed on Asian population. [13][14][15][44][45][46][47] As potential limitations of this study, the use of medical records as source for the assessed outcomes could have led to a loss of information. This information bias was managed by contacting each subject by phone as possible and ensure that the data in medical records were precise.…”
Section: Discussionmentioning
confidence: 99%
“…The only exception was the study reported by Sharma, which did not show any statistical significance in the association (Sharma et al, 2011). Two studies reported an intervention with treatment (Eltas et al, 2013; Lee et al, 2017). The reasons why studies were not included in the current are available in Table 3.…”
Section: Discussionmentioning
confidence: 99%